THE SPECTRUM OF STUDENT ENROLLMENT-RELATED OUTCOMES IN PHYSIOTHERAPY EDUCATION PROGRAMS IN WEST AFRICA (International Journal of Physiotherapy, 2016)
Background: This cross-sectional study investigated student enrollment-related outcomes from physiotherapy education programs in West Africa.Methods: The Head of Department of all physiotherapy education programs in Nigeria and Ghana universities (N=14) completed a questionnaire that sought information on admission capacity/goal, student enrollment, baccalaureate (BPT/BS) and postgraduate (MS, Ph.D.) degrees conferred and the student-core faculty ratio (SFR).Results: In Nigeria, 4,748 BPT, 325 MS and 50 Ph.D. degrees in physiotherapy were conferred over a 50 year period; 2,038 BPT, 160 MS, and 42 Ph.D. students are currently enrolled. In Ghana, over a 14 year period, 277 BS degrees were conferred and 162 students are currently enrolled. The mean SFR for the undergraduate program in Nigeria and Ghana was 17.6 and 13.5, respectively. In Nigeria, 83.3% of the physiotherapy programs are located in Federal owned university; while in Ghana 100% of the programs are in State-owned university (χ² = 8.556; p =.014). Admission goal and university ownership are significantly (p